Estudo numérico do acoplador duplo simétrico de fibras ópticas operando com PPM e PAM para obtenção de portas lógicas - Ferreira, Alisson da Conceição (2008)
In this work, the performance study of a Symmetric Dual-Core Non-Linear Directional Coupler (NLDC), working with pulses of , in two different applications have been investigated: accomplishment of logical gates AND and OR, under Pulse Position Modulation (PPM); accomplishment of logical gates AND and OR, under Pulse Amplitude Modulation (PAM). The investigation is based in a numerical simulation study, using the fourth order Runge Kutta numerical method. In the first application, the possibility of the accomplishment of logical operations by Symmetric Dual-Core Non-Linear Directional Coupler (NLDC) without loss is analyzed. Considering the operation of the logical gates, the four possible combinations for two pulses, on the input fibers, modulated by the temporal PPM in the logical levels 0 or 1, were used. The effects of a variation in the coding parameter offset of the PPM modulation, that is, in the displacement of the input pulse relative to the reference time level, was investigated. In the second application, the symmetric dual-core NLDC is submitted to PAM modulation, using the four possible combinations for two pulses on the input fibers, were used, as well. The effects of a variation in the coding parameter offset of the PAM modulation relative to the reference amplitude, was investigated. The modulated output amplitude versus a phase difference between the input pulses , was also studied. On the two applications, logical gates AND and OR was observed.